Study on the influence of working environment on the insulation of fuel cell - Ji Pu; Qianya Xie; Kang Li; Jun Li; Mengmeng Zhang; Chen Ge; Lichang Zhang (Heliyon)
Fuel cell engines have been widely studied as an efficient energy conversion technology because of their clean and renewable characteristics. The insulation of a fuel cell engine is one of the key factors that ensure its performance and safety. As the core assembly of a vehicle, the fuel cell engine directly affects the efficiency and stability of the vehicle power system. Most studies have analyzed the coolant conductivity, coolant temperature, and ion precipitation of the components. Based on the improvement of insulation in previous studies, this study uses multi-stack proton exchange membrane(PEM) fuel cells used in commercial vehicles as an example to analyze the influence of ambient relative humidity(RH) on the insulation of fuel cells through a combination of tests and fluid simulations. The results show that the insulation resistance(IR) of the stack decreases abruptly with an increase in the ambient relative humidity. The insulation was better when the ambient relative humidity was lower than 60 %. When the cooling water temperature or conductivity increased, the insulation of the stack tended to decrease, and the conductivity had a greater impact on the insulation of the stack. When the pipe diameter of the purge shell was designed to be approximately 20 % of the main pipe diameter, the relative humidity of fresh air entering the shell was lower than 60 % when the ambient relative humidity outside the shell was 95 %. A gap of at least 15 mm should be left between the stacks to avoid residual liquid water condensed by the temperature change of the stack in the small gap. The creepage distance and dielectric strength of fuel cell end plate and insulation plate under high relative humidity are analyzed, and the improvement measures are put forward. These research results are critical for advancing commercial applications.